Increased temperature causes different carbon and nitrogen processing patterns in two common intertidal foraminifera (Ammonia tepida and Haynesina germanica) - J. Wukovits; A. J. Enge; W. Wanek; M. Watzka; P. Heinz (Biogeosciences, 2017)
Benthic foraminifera are highly abundant heterotrophic protists in marine sediments, but future environmental changes will challenge the tolerance limits of intertidal species. Metabolic rates and physiological processes in foraminifera are strongly dependent on environmental temperatures. Temperature-related stress could therefore impact foraminiferal food source processing efficiency and might result in altered nutrient fluxes through the intertidal food web. In this study, we performed a laboratory feeding experiment on Ammonia tepida and Haynesina germanica, two dominant foraminiferal species of the German Wadden Sea/Friedrichskoog, to test the effect of temperature on phytodetritus retention. The specimens were fed with 13C and 15N labelled freeze-dried Dunaliella tertiolecta (green algae) at the start of the experiment and were incubated at 20, 25 and 30 °C respectively. Dual labelling was applied to observe potential temperature effects on the relation of phytodetrital carbon and nitrogen retention. Samples were taken over a period of 2 weeks. Foraminiferal cytoplasm was isotopically analysed to investigate differences in carbon and nitrogen uptake derived from the food source. Both species showed a positive response to the provided food source, but carbon uptake rates of A. tepida were 10-fold higher compared to those of H. germanica. Increased temperatures had a far stronger impact on the carbon uptake of H. germanica than on A. tepida. A distinct increase in the levels of phytodetrital-derived nitrogen (compared to more steady carbon levels) could be observed over the course of the experiment in both species. The results suggest that higher temperatures have a significant negative effect on the carbon exploitation of H. germanica. For A. tepida, higher carbon uptake rates and the enhanced tolerance range for higher temperatures could outline an advantage in warmer periods if the main food source consists of chlorophyte phytodetritus. These conditions are likely to impact nutrient fluxes in A. tepida/H. germanica associations.